2020
DOI: 10.1007/s42452-020-2703-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate contents of Thai rice paddy herbs (L. aromatica and L. geoffrayi) are affected by drying method and changes after cooking

Abstract: Food processing, including drying and cooking, generally influences the physical and chemical qualities of food products. The present study assessed the changes in oxalate contents of two rice paddy herbs (phak-kha-yaeng in Thai), Limnophila aromatica (phak-kha-yaeng khao) and Limnophila geoffrayi (phak-kha-yaeng daeng), as affected by different drying methods, namely hot-air, freeze and vacuum drying. The entire, soluble and insoluble oxalate contents of the cooked samples were also evaluated. Dried samples s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The non-defective flours have an antioxidant content that ranges from 23.671 µmol/g (traditionally dried flour in year 2) to 55.890 µmol/g (dried at 40 • C hot air in year 1), indicating a marked influence of the drying method on this variable. Other previous studies, indeed, demonstrated that the drying temperature affects the morphological and chemical properties of chestnut flours [1], and in rice paddy herbs there are differences in phenolic compounds and antioxidant properties as well [35]. In our study, if only non-defective flours are considered, the chestnut flours dried with hot air at 70 • C and 40 • C, for both years, present higher values at around 50 µmol/g.…”
Section: Determination Of Antioxidant Powersupporting
confidence: 61%
See 1 more Smart Citation
“…The non-defective flours have an antioxidant content that ranges from 23.671 µmol/g (traditionally dried flour in year 2) to 55.890 µmol/g (dried at 40 • C hot air in year 1), indicating a marked influence of the drying method on this variable. Other previous studies, indeed, demonstrated that the drying temperature affects the morphological and chemical properties of chestnut flours [1], and in rice paddy herbs there are differences in phenolic compounds and antioxidant properties as well [35]. In our study, if only non-defective flours are considered, the chestnut flours dried with hot air at 70 • C and 40 • C, for both years, present higher values at around 50 µmol/g.…”
Section: Determination Of Antioxidant Powersupporting
confidence: 61%
“…chestnut flours [1], and in rice paddy herbs there are differences in phenolic compounds and antioxidant properties as well [35]. In our study, if only non-defective flours are considered, the chestnut flours dried with hot air at 70 °C and 40 °C, for both years, present higher values at around 50 µmol/g.…”
Section: Determination Of Antioxidant Powermentioning
confidence: 51%